Procedencia de las medidas cautelares como garantía constitucional de protección - Cevallos Pachacama, Nathaly Zulema (2014)
Since the creation of the precautionary measures with the Roman Law, which seek the protection of the different rights of the people, the precautionary measures as the rest of the constitutional guaranties have existed in our country since the extinct Political Constitution of the Republic of 1998, but they only had a precautionary character, meaning they only protected, while in the present days they have a declarative character of knowledge and over all they compensate. Meaning that in the actual Political Constitution (2008), the precautionary measures stablish a constitutional guaranty, with an autonomous procedure, which means they do not require of a previous judicial process to be requested, however, the norm also stablishes the possibility of requesting this measure jointly with other principal jurisdictional guaranty. The next work will analyze the precautionary measures in four chapters, since its beginning through the times, followed by its definitions and the difference on the different Constitutions that existed in our country after the return of democracy, the precautionary measures in the different areas of law, its origin, application and finally its real value. Witch will aloud the target of this investigation, determining the necessity and origin of the precautionary measures as a constitutional guaranty, beside identifying the obstacles that will not allowed the efficiency of the protection of human rights, to guaranty the remedy with a simple and brief system, seeking the ideal of justice.